(untitled) (Research, Society and Development, 2022)
The aim of the present study is to validate an instrument to assess the satisfaction of students in distance education in Brazil. Based on this assumption, using the instrument of Sun et al. (2008), the cross-cultural adaptation and validation for the Brazilian context was carried out, having as research population 1,103 students enrolled in undergraduate and graduate courses in the Distance Education (DE) modality at the University Open of Brazil (UOB). Using the partial structural equations method based on variances - Partial Least Squares Structural Equation Modeling (PLS-SEM), each construct present in the original instrument was evaluated to verify the validity within the determined study environment. After the analyzes carried out, 22 questions were eliminated, which did not present enough factor loads to have convergent validity of the model. Thus, it resulted in an instrument valid in Brazil, containing 40 questions arranged in 7 dimensions that aim to collaborate with the theme of student satisfaction in the distance learning environment.